2020
DOI: 10.1186/s12885-020-07637-z
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of exercise training and nutritional support prior to haematopoietic stem cell transplantation in patients with haematologic malignancies

Abstract: Background Prehabilitation with regular exercise and nutritional care for patients undergoing surgeries for malignant disease was recently introduced to increase physiologic reserve prior to the procedure, accelerate recovery and improve outcomes. This study aimed to investigate the feasibility and safety of combined exercise training and nutritional support in patients with haematologic malignancies prior to haematopoietic stem cell transplantation (HSCT). Methods In this single-arm pilot study, 34 HSCT cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 30 publications
2
31
0
Order By: Relevance
“…Of these, we assessed n = 195 for eligibility based on the full text. A total of n = 39 studies of the following types met the inclusion criteria [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]: n = 24 randomized clinical trials, n = 9 pilot studies, and n = 6 feasibility studies ( Table 1 ). In these 39 studies, n = 84 different outcomes were used 227 times and were measured using n = 125 different instruments ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, we assessed n = 195 for eligibility based on the full text. A total of n = 39 studies of the following types met the inclusion criteria [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]: n = 24 randomized clinical trials, n = 9 pilot studies, and n = 6 feasibility studies ( Table 1 ). In these 39 studies, n = 84 different outcomes were used 227 times and were measured using n = 125 different instruments ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In these 39 studies, n = 84 different outcomes were used 227 times and were measured using n = 125 different instruments (Table 2). Adherence [16] Adverse Events [16] Program completion from 50% of the patients [17] Recruitment [16] Feasibility Pilot Study [17] Hospital [17] Exercise [16,17] Santa mina et al Feasibility [18][19][20] Pilot Study [21,25] Hospital [18][19][20] Outpatient post [21] Outpatient pre [25] Electric Muscle Stimulation [18] Healing touch [19] Inspiratory muscle training [20] Home based aerobic exercise [6] Exercise Training and Nutritional Support [25] Bewarder et al Attrition [20,21,25,27] Feasibility [20] Pilot Study [21,25] Hospital [20] Outpatient post [21] Outpatient pre [25] Inspiratory muscle training [20] Home based aerobic exercise [21] Exercise Training and Nutritional Support [25] De almeida et al Retention [19,22] Feasibility [19,22] Hospital [19] Outpatient post [22] Healing touch…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rehabilitation for patients undergoing HSCT is generally aimed at preventing the deterioration of physical function and improving the quality of life. 15 ) A recent study 16 ) reported the feasibility and safety of combined exercise training and nutritional support before HSCT in patients with hematologic malignancies. The present case suggested that combined exercise training and nutritional support aimed at weight loss could be feasible and safe in patients with hematologic malignancies.…”
Section: Discussionmentioning
confidence: 99%